PEMAKAIAN BAHASA DALAM KELUARGA MULTIETNIS DI DESA SANUR - suparwa, nyoman (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2017)
This study aims to describe the use of language in multi-ethnic family in Sanur village of South Denpasar, Bali. The description includes (1) the use of language in multi-ethnic family, (2) the function of Indonesian language in the multi-ethnic family, (3) Linguistics constraints faced by multi-ethnic families in Sanur in the communication, both within the family and outside the family. This study uses socio-pragmatics theory that is sociolinguistics theory which sees the language to be in touch with the community of native speakers. Therefore, language is always heterogeneous (not homogeneous) because of the community diversity of the language speakers. Then, the theory is combined with the pragmatic theory that studies how significant   data in this study is a field method and the method of analysis is descriptive method. This study found that (1) Based on various situation of language usage, the lagunage used are (a) Indonesian language is used in formal situation   Indonesian language mixed with Balinese language are used in non-formal and emotional situation and also when the dialogue happened in the family   Indonesian language is used in the o?ce, public health center and school. Meanwhile, within the family, wedding or funerals ceremony and shopping in the market, they use Indonesian language mixed with local and foreign language. Then, in the family meeting and in emotional situation, they use local language (Balinese), and for greeting the neighbor on the street, they use mixed language (Balinese and Indonesian language). Finally, in the religious situation, such as communication situation of personal relationship to the God, they use Indonesian language mixed with the religion language (spell, Arabic, and Japanese). (3) The communication constraints in multi-ethnic family such as the language in the beginning of communication and also di?erent culture and religion.   Keywords : language use, the function of Indonesian language, multi-ethnic family